Piscidin-1-analogs with double L- and D-lysine residues exhibited different conformations in lipopolysaccharide but comparable anti-endotoxin activities - Kumar, Amit (2017)
To become clinically effective, antimicrobial peptides (AMPs) should be non-cytotoxic to host cells. Piscidins are a group of fish-derived AMPs with potent antimicrobial and antiendotoxin activities but limited by extreme cytotoxicity. We conjectured that introduction of cationic residue(s) at the interface of polar and non-polar faces of piscidins may control their insertion into hydrophobic mammalian cell membrane and thereby reducing cytotoxicity. We have designed several novel analogs of piscidin-1 by substituting threonine residue(s) with L and D-lysine residue(s). L/D-lysine-substituted analogs showed significantly reduced cytotoxicity but exhibited either higher or comparable antibacterial activity akin to piscidin-1. Piscidin-1-analogs demonstrated higher efficacy than piscidin-1 in inhibiting lipopolysaccharide (LPS)-induced pro-inflammatory responses in THP-1 cells. T15,21K-piscidin-1 (0.5 mg/Kg) and T15,21dK-piscidin-1 (1.0 mg/Kg) demonstrated 100% survival of LPS (12.0 mg/Kg)-administered mice. High resolution NMR studies revealed that both piscidin-1 and T15,21K-piscidin-1 adopted helical structures, with latter showing a shorter helix, higher amphipathicity and cationic residues placed at optimal distances to form ionic/hydrogen bond with lipid A of LPS. Remarkably, T15,21dK-piscidin-1 showed a helix-loop-helix structure in LPS and its interactions with LPS could be sustained by the distance of separation of side chains of R7 and D-Lys-15 which is close to the inter-phosphate distance of lipid A.